Pengaruh Digitalisasi Dalam Bidang E-Commerce Terhadap Perilaku Konsumtif Mahasiswa UIN Sunan Ampel - Sefiya Nur Farichin (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2022)
Abstract-- This study aims to determine the effect of digitalization in the field of e-commerce on the consumptive behavior of students at UIN Sunan Ampel Surabaya. The analytical method used in this study is a qualitative descriptive method using questionnaires and interviews via WhatsApp to obtain valid data and information from 22 respondents. The results show that all respondents have an e-commerce platform application that can be accessed intensively through gadgets and all respondents have done consumptive behavior, namely by transacting goods that are not needed. So, the factors that cause this behavior include the large number of discounts offered and the influence of advertisements on social media Keywords: Student Consumptive Behavior, E-Commerce, Digitization